The productive partnership in development communication is an effective strategy for change (Journal of Planner and Development, 2006)
This study can be considered as un introduction to the idioms and the strategy about the productive partnership development connection, that helps the researcher and the organization in their work in to activate development and the natural sources,manegment,to improve the two sides active connected to the local society, and to use it as easier and smoother participation of the people who work in development field and the natural sources management research, That connection depends mostly upon the capability of researcher and the development worker to increase the ability of individual and local society to specify and analyzing their problems and to try solutions to make their life better with good income.